PROBLEMS ARE CAUSED TO CHANGE TYPICAL TEMPORARY LOADS AC FOR BRIDGES CONSTRUCTIONS - Salamakhin, P. M. (Science and Transport Progress, 2010)
The article is devoted to the analysis of new temporal normative loads of high-way bridges, the determination of dynamic coefficient and the problems of the using these loads in calculation of endurance and determination of remaining resource of elements of bridge structures.